2013
DOI: 10.1371/journal.pone.0061370
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in the Prevalence of Sand Flies Infected with Leishmania donovani

Abstract: BackgroundVisceral Leishmaniasis (VL) is a life threatening neglected infectious disease in the Indian subcontinent, transmitted by the bite of female sand flies. Estimation of the infectivity in the vector population, collected in different seasons, may be useful to better understanding the transmission dynamics of VL as well as to plan vector control measures.MethodologyWe collected sand flies from highly endemic regions of Bihar state, India for one year over three seasons. The species of the sand flies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 25 publications
(31 reference statements)
3
35
0
2
Order By: Relevance
“…Dhanda and Modi (1971) from Aurangabad district, Maharashtra and Joseph (1981) from Kala azar affected areas of northern districts of Bihar and Tiwary et al (2013) from VL endemic areas of Muzaffarpur in Bihar, India substantiated that sand flies were abundant with a single peak in monsoon month of October. In the present investigation, sand flies including P. argentipes were found prevalent throughout the year, with two peaks, a minor peak in June/July which was in the south-west monsoon period and a major peak in October, in northeast monsoon season, where there was no winter season, however, the month the period between December and February were relatively cooler in this region.…”
Section: Discussionmentioning
confidence: 97%
“…Dhanda and Modi (1971) from Aurangabad district, Maharashtra and Joseph (1981) from Kala azar affected areas of northern districts of Bihar and Tiwary et al (2013) from VL endemic areas of Muzaffarpur in Bihar, India substantiated that sand flies were abundant with a single peak in monsoon month of October. In the present investigation, sand flies including P. argentipes were found prevalent throughout the year, with two peaks, a minor peak in June/July which was in the south-west monsoon period and a major peak in October, in northeast monsoon season, where there was no winter season, however, the month the period between December and February were relatively cooler in this region.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, on the ISC, Picado et al (2010a) argue that IRS should be carried out in Feb/March and August/September based on seasonal patterns observed in their sandfly density studies in India and Nepal. However a study in Bihar, India which examined sandfly infection as well as density found that whilst abundance was highest during August/September, prevalence in sandflies was greatest in November/December (Tiwary et al, 2013). Such results warrant further investigation into the seasonality in all endemic regions, especially when planning the timing of vector interventions such as IRS.…”
Section: Seasonality Of Sandfliesmentioning
confidence: 96%
“…were 1.0 % (4/384) in summer 0.8 % (5/591) in the rainy season, and 2.8 % (12/422) in winter (Tiwary, Kumar et al 2013 (Guimaraes, Costa et al 2014). …”
Section: Infection Rate Of Infectious Life Stagesmentioning
confidence: 97%